Experimental measurement of respiratory particles dispersed by wind instruments and analysis of the associated risk of infection transmission. (January 2023) - Schlenczek, Oliver; Thiede, Birte; Turco, Laura; Stieger, Katja; Kosub, Jana M.; Müller, Rudolf; Scheithauer, Simone; Bodenschatz, Eberhard; Bagheri, Gholamhossein
Abstract: Activities such as singing or playing a wind instrument release respiratory particles into the air that may contain pathogens and thus pose a risk for infection transmission. Here we report measurements of the size distribution, number, and volume concentration of exhaled particles from 31 healthy musicians playing 20 types of wind instruments using aerosol size spectrometry complemented with in-line holography in a strictly controlled cleanroom environment. We find that playing wind instruments carries a lower risk of airborne disease transmission than speaking or singing. We attribute this to the fact that the resonators of wind instruments act as filters for particles > 10 µm in diameter, which were found in high abundance right after a brass mouthpiece but very rarely at the instrument bell end. We have also measured the size-dependent filtering properties of different types of filters that can be used as instrument masks. Based on these measurements, we calculated the risk of airborne transmission of SARS-CoV-2 in different near- and far-field scenarios with and without masking and/or distancing. We conclude that in all cases where there is a possibility that the musician is infectious, the only safe measure to prevent airborne transmission of the disease is the use of well-fitting and well-filtering masks for the instrument and the susceptible person. Highlights: Particle emission measured on 20 wind instrument types under controlled conditions. Emitted particle volume concentration mostly between normal breathing and speaking. Upper bound of risk for SARS CoV-2 infection transmission for near- and far-field. Universal masking found to yield the best protection against infection transmission. Graphical abstract: